EFFICACY OF MULTI-STRAIN PROBIOTICS ON GROWTH PERFORMANCE, FEED UTILIZATION, PROXIMATE COMPOSITION, AND HAEMATOLOGICAL PARAMETERS OF ASIAN CATFISH (Clarias batrachus) JUVENILES - Md. Raihan Ahmed; Mst. Nahid Akter; Sheik Istiak Md. Shahriar; Moumita Habiba Sarmin Dorin; Akhtaruzzaman Akhtaruzzaman; Md. Mehedi Hasan (Indonesian Aquaculture Journal, 2026)
This study was conducted to determine the effects of different commercial probiotics on the growth performance, feed utilization, proximate composition, and haematological parameters of Asian catfish (Clarias batrachus) juveniles. The study design consists of a total of 300 fish (avg. wt. 11.14±0.5 g) randomly distributed in twelve tanks with a stocking density of 25 fish/tank. Fish diets were formulated using 0.2% of three different commercial probiotics namely T1, CP-1; T2, CP-2; and T3, CP-3, and a control diet without probiotics. Fishes were fed at a rate of 3% body weight twice daily. The growth performance indicators i.e. final body weight (g), weight gain (g) and specific growth rate (%/day), were found to be highest in T3 (CP-3) and were significantly different from the others. Similarly, feed utilization (feed conversion ratio) was significantly improved in fish fed 0.2% probiotic diet. Among body indice parameters, intra peritoneal fat (%) reduced significantly in probiotic fed groups. Besides, highest percentage of protein (79.52±0.61) and lowest lipid content (6.14±0.25) were recorded in T3 (CP-3) supplemented diet. Haematological parameters especially percentage of packed cell volume and white blood cell were escalated in T1 (CP-1) and T3 (CP-3) whereas mean corpuscular volume found comparatively lower in control. Therefore, finally the results of principal component analysis concluded that the incorporation of probiotic T3 (CP-3) at 0.2% in diet proved more effective for the improvement of growth performance, proximate composition and haematological parameters for C. batrachus juvenile farming.